2010
DOI: 10.3109/00016480902896147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MRI contrast agents (Omniscan™) on vestibular end organs

Abstract: Application of 4-16-fold diluted Omniscan caused morphological damage of isolated vestibular hair cells and decreased action potentials of the posterior semicircular canal. After application of 32-fold diluted Omniscan, no apparent changes were noted even after 20 min, both morphologically and physiologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Animal studies from Tanaka et al showed morphological changes such as shape changing, hair cell impairment, and cell shrinkage in vestibular end organs of bullfrogs after application of fourfold diluted GBCA. With the eightfold and sixteenfold dilution, the morphological changes were less frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies from Tanaka et al showed morphological changes such as shape changing, hair cell impairment, and cell shrinkage in vestibular end organs of bullfrogs after application of fourfold diluted GBCA. With the eightfold and sixteenfold dilution, the morphological changes were less frequent.…”
Section: Discussionmentioning
confidence: 99%